Some aspects on modelling of the β-phase depletion behaviour under different oxide growth kinetics in HVOF CoNiCrAlY coatings - Chen, H.; McCartney, D.G. (Elsevier, 2017)
In this paper, β-phase depletion behaviour of free-standing high velocity oxy-fuel (HVOF) thermally sprayed CoNiCrAlY coatings was studied. Microstructural analysis showed a two-phase microstructure of γ-Ni matrix and β-NiAl secondary phase after heat treatment. Fine grains were found around the sprayed particle boundaries and coarse grains were retained as the original particle structure, with grain sizes varying from 2 to 0.5 μm or even less for both phases. The β-phase depletion behaviour was investigated during isothermal oxidation and was also modelled through diffusion calculations. A previously developed β-phase depletion model was utilised to study the evolution of β-phase depletion under different oxide growth kinetics. Three oxide growth models were tried: 1) Meier model, 2) thermogravimetric analysis (TGA) model, and 3) experimentally fitted oxide growth model. The oxide growth kinetics were converted to Al flux functions which were used as the boundary conditions in the DICTRA modelling. It is shown that the results obtained from the three models exhibit good agreements between the measured and predicted results for times up to 100 h at 1100 C, but discrepancies were noted at longer oxidation times. Further improvements on closely modelling the oxidation kinetics and the effective diffusion behaviour are needed to minimise the discrepancies at longer oxidation times.